DEVELOPMENT OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM)-BASED E-BOOK ON HUMAN DIGESTIVE SYSTEM MATERIAL BASED ON SCIENTIFIC LITERACY - Sihombing, Rizky Agassy; Hasruddin, Hasruddin (Universitas Tanjungpura, 2024)
Abstract The research was conducted on students